1999
DOI: 10.1029/1999jd900827
|View full text |Cite
|
Sign up to set email alerts
|

Choosing meteorological input for the global modeling initiative assessment of high‐speed aircraft

Abstract: Abstract. The global modeling initiative (GMI) science team is developing a three-dimensional chemistry and transport model (CTM) for use in assessment of the atmospheric effects of aviation. This model must be documented, be validated against observations, use a realistic atmospheric circulation, and contain numerical transport and photochemical modules representing atmospheric processes. The model must retain computational eificiency for multiple scenarios and sensitivity studies. To meet these requirements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 46 publications
1
105
0
Order By: Relevance
“…by Hall et al [1999], the mean age at a location in the stratosphere for a constituent such as SF6 with a steady tropospheric trend is the difference between the time of a measurement and the time in the tropospheric time series when the measured value matches the troposphere value. The age of air is determined using CTMwc, cM and…”
Section: As Discussedmentioning
confidence: 99%
See 1 more Smart Citation
“…by Hall et al [1999], the mean age at a location in the stratosphere for a constituent such as SF6 with a steady tropospheric trend is the difference between the time of a measurement and the time in the tropospheric time series when the measured value matches the troposphere value. The age of air is determined using CTMwc, cM and…”
Section: As Discussedmentioning
confidence: 99%
“…The mean age, the mass weighted average of the transit times from the tropical tropopause to any given location, is a sensitive diagnostic of model transport [Hall and Plumb, 1994;Hall et al, 1999]. Model calculations of mean age were compared with the age determined from observations of SF 6 and CO2 as part of Models and Measurements Intercomparison II [Park et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…The use of different meteorological fields in driving chemical transport models can lead to diverging distributions of chemical species in the upper troposphere/lower stratosphere (UTLS) region (Douglass et al, 1999). Several studies based on multi-year CTM simulations have shown that vertical winds directly supplied from analyses can result in an overprediction of the strength of the stratospheric circulation and an under-prediction of the age of air (Chipperfield, 2006;Monge-Sanz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The numerical experiment is straightforward. With a specified pattern of constant surface emissions, we follow the buildup and dispersion of fossil-fuel CO 2 (21) as a conserved tracer throughout the atmosphere for 10 years by cycling 1 year of archived meteorological fields from the Goddard Institute for Space Studies middle atmosphere model (14,22). Two scientific applications are addressed.…”
mentioning
confidence: 99%